COMPREHENSIVE REVIEW OF TREATMENT OPTIONS FOR ERECTILE DYSFUNCTION: MODERN AND TRADITIONAL METHODS - Oskar Sienkiel,; Agnieszka Fitas,; Wojciech Gąska,; Julia Głowacka,; Mathias Spitaleri,; Filip Kieloch,; Dawid Sewruk,; Wiktor Gąska,; Karol Kanon,; Karolina Dębek-Kalinowska, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Erectile dysfunction (ED), or impotence, is a condition where a man can't get or keep an erection firm enough for satisfying sexual intercourse. It affects men of all ages and is caused by a variety of physical, psychological, or social factors. The number of ED cases is growing annually, and treatment costs are rising steadily. This combination of increasing prevalence and rising expenses highlights the need for a highly optimized treatment method. Efforts should focus on finding a solution that is as effective as possible while also being cost-efficient. The goal is to provide accessible, high-quality care without the financial burden, ensuring that men who suffer from this condition can find relief and improve their quality of life. The search for such a method is crucial given the growing impact of ED on men worldwide.Aim: The aim of this study was to review literature studies on ED and methods for treating this condition. Method: Data for the article were retrieved by using Pub Med setting the time descriptor to 2020-2025.Conclusions: Despite the availability of many effective treatments for erectile dysfunction (ED), it can still be a challenging condition due to the variety of underlying causes. Therefore, an individualized approach and thorough diagnostics are essential. Regenerative therapies and shockwave therapy, although still experimental, offer new therapeutic opportunities. In the future, it will be important to conduct randomized studies with long-term follow-up to assess the effectiveness and safety of these new methods.